HUBUNGAN KONFLIK PERAN PADA KOMITMEN ORGANISASI: KEPUASAN DAN STRES KERJA SEBAGAI VARIABEL MEDIASI - Kurniawan, Fatah; Cahyono, Edi (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2014)
The purpose of this study is to investigate the role theory and related to affective commitment as dependence variable at volunteerâs organizations, and examine the causal pattern of relationships among role conflict, stress, job satisaction, and affective commitment. The participans of this study were 230 volunteers in Sukoharjo. Sampling technique with purposive sampling method. The statistical methods used to test the validity, reliability, and the research hypothesis is Structural Equation Modeling (SEM) Analysis. Result of this research indicates that role conflict has correlation with stress and job satisfaction, both directly. Yet, stress doesnât mediating between role conflict and volunteerâs satisfaction. Another finding was a correlation between job satisfaction and affective commitment. Conclude that role theory application in volunteers organization hasnât similiar finding with another study, and the author recommend another study at vast volunteers or non profitable organizations.